2021
DOI: 10.1016/j.jth.2021.101264
|View full text |Cite
|
Sign up to set email alerts
|

Should bike-sharing continue operating during the COVID-19 pandemic? Empirical findings from Nanjing, China

Abstract: Introduction Coronavirus disease 2019 (COVID-19) has triggered a worldwide outbreak of pandemic, and transportation services have played a key role in coronavirus transmission. Although not crowded in a confined space like a bus or a metro car, bike-sharing users are exposed to the bike surface and take the transmission risk. During the COVID-19 pandemic, how to meet user demand and avoid virus spreading has become an important issue for bike-sharing. Methods Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…Similar results to our research were found and conclusions were extracted for the cities of New York [37,38], Budapest [39], Thessaloniki [40,41], Nanjing [42], and the region of Sicily in Italy [43], regarding the level of ridership before, during, and after the imposition of restricting measures concerning urban mobility and specifically the usage of bicycles, the rides' duration [44], the people's perception towards BS systems due to the COVID-19 pandemic, and to bicycles in general [45,46]. Furthermore, during the early stages of the pandemic, in some cases, bike sharing expanded their memberships or improved accessibility for specific working groups [47].…”
Section: Discussionsupporting
confidence: 91%
“…Similar results to our research were found and conclusions were extracted for the cities of New York [37,38], Budapest [39], Thessaloniki [40,41], Nanjing [42], and the region of Sicily in Italy [43], regarding the level of ridership before, during, and after the imposition of restricting measures concerning urban mobility and specifically the usage of bicycles, the rides' duration [44], the people's perception towards BS systems due to the COVID-19 pandemic, and to bicycles in general [45,46]. Furthermore, during the early stages of the pandemic, in some cases, bike sharing expanded their memberships or improved accessibility for specific working groups [47].…”
Section: Discussionsupporting
confidence: 91%
“…Before COVID-19, there were some studies that aimed to capture the influences of epidemic events on traditional transport modes ( Cui et al, 2011 ; Zhang et al, 2011 ). As an alternative mode of transport with its advantage in social distancing, a shared bike serves as a lifeline to satisfy the daily mobility demand of people during the COVID-19 pandemic ( Shokouhyar et al, 2021 ; Hua et al, 2021 ). However, it's the first pandemic strike since the emergence of bike sharing systems.…”
Section: Introductionmentioning
confidence: 99%
“…It’s worth noting that technologies like Sharing Economy have more obvious contributions in this stage. The development and maturation of massive virtual mobile applications and sharing ideas such as shared travel and shared employment will reduce the impact of the pandemic lockdown through the expansion of flexible virtual spaces and the efficient reuse of physical spaces and resources (Hua et al, 2021).…”
Section: Resultsmentioning
confidence: 99%